(3GdEUdGM GdEOGQj hGdJWhjQ GdeDSSj aj GdYGde GdYQHj aj Xd GdJMOjGJ GdEbJUGOjI GdLOjOIs - (3fRjg(B, (3GdCjhHjs ((3GdbGgQI(B:s (3GdefXeI GdYQHjI ddJfejI GdEOGQjI(B,s, 1995)
(3GdEUdGM hGdJWhjQ GdEOGQj ,GdJWhjQ GdEOGQj dOYe GdcaGAI GdEbJUGOjI hGdLhGfH GdJfXjejI hGdEOGQjI ddNhUIs
(3GdeQGLY U(B.80s
Keywords: (3GdEOGQI (B- (3JWhjQs; (3GdEUdGM GdEOGQjs